2010
DOI: 10.1177/0363546510382206
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study Comparing Arthroscopic Single-Bundle and Double-Bundle Posterior Cruciate Ligament Reconstructions Preserving Remnant Fibers

Abstract: The DB reconstruction for PCL ruptures using the Achilles allograft showed better results in posterior stability and IKDC knee examination form than the SB reconstruction did. Although the difference of 1.4 mm in posterior stability was statistically significant, it is unclear that DB reconstruction is definitely superior to SB reconstruction clinically and functionally because there was no difference in the subjective scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
137
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 32 publications
(44 reference statements)
2
137
2
2
Order By: Relevance
“…A further study was judged to have a high risk of performance bias and detection bias (all procedures and outcome assessments were performed by the same author). 20 In two studies, over 5% of patients were lost to follow-up. 20,22 A single study reported adequately generated allocation concealment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A further study was judged to have a high risk of performance bias and detection bias (all procedures and outcome assessments were performed by the same author). 20 In two studies, over 5% of patients were lost to follow-up. 20,22 A single study reported adequately generated allocation concealment.…”
Section: Resultsmentioning
confidence: 99%
“…20 In two studies, over 5% of patients were lost to follow-up. 20,22 A single study reported adequately generated allocation concealment. 22 MINORS quality scores of non-RCTs are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations